Los archivos del poder legislativo - Maciá, Mateo; Valle de Juan, Mª Ángeles (Revista General de Información y Documentación, 2002)
The history, resources and functions of the Archives of the Cortes Generales (1810-1834), the Senate (1834) and the Congress of Representatives are studied. Also included is a description of work in process.
Keywords: Parliamentary archive; Parliamentary administration; History of parliament; Political history; Spain